Terrestrial algae: pioneer organisms of carbonate rock solutional weathering in South China karst - Yan, Ni; Zhao, Jiawei; Xiong, Kangning; Yang, Chunliu; Li, Junqin; Chen, Qian (Frontiers in Microbiology, 2024)
The formation of soil in karst ecosystem has always been a scientific problem of great concern to human beings. Algae can grow on the exposed and non-nutrition carbonate surface, inducing and accelerating weathering of rock substrates, thus promoting soil formation. Yet the actual contribution of algae to solutional weathering intensity remains unclear. In this study, we performed weathering simulation experiment on two algae species (Klebsormidium dissectum (F.Gay) H.Ettl & G.Gä rtner and Chlorella vulgaris Beijerinck), which were screened from carbonated rock surfaces from a typical karst region in South China . The results showed: (1) both algae have solutional weathering effect on carbonate rock, (2) there is no difference of solutional intensity observed, yet the solutional modes are different, suggesting different ecological adaptative strategies, (3) algae on carbonate rocks have higher carbonic anhydrase activity (CAA) and secrete more extracellular polysaccharide (EPS), accelerating rock weathering. (4) The absolute dissolution amount of carbonate rock with algae participation is 3 times of that of without algae.These results indicate the significant impact of terrestrial algae on carbonate rock solutional weathering and provides quantitative evidence that terrestrial algae are pioneer species. It also contributes to our further understanding of soil formation in karst ecosystems in South China.